2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091831
|View full text |Cite
|
Sign up to set email alerts
|

Online feedback control of functional electrical stimulation using dorsal root ganglia recordings

Abstract: In neuroprostheses that use functional electrical stimulation (FES) to restore motor function, closed-loop feedback control may compensate for muscle fatigue, perturbations and nonlinearities in the behavior of the effected muscles. Kinematic state information is naturally represented in the firing rates of primary afferent neurons, which may be recorded with multi-electrode arrays at the level of the dorsal root ganglia (DRG). Previous work in cats has shown that it is feasible to estimate the kinematic state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Most artifacts were automatically rejected by the clustering algorithm. In addition, a simple artifact rejection algorithm was implemented in the RZ2 processor, as described in [34]. Briefly, if the sum of spike-threshold crossing events across all channels during a 400 µs detection window exceeded a set limit (54 channels; 60%) then all events in a corresponding 2 ms rejection window were excluded from the spike count vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most artifacts were automatically rejected by the clustering algorithm. In addition, a simple artifact rejection algorithm was implemented in the RZ2 processor, as described in [34]. Briefly, if the sum of spike-threshold crossing events across all channels during a 400 µs detection window exceeded a set limit (54 channels; 60%) then all events in a corresponding 2 ms rejection window were excluded from the spike count vector.…”
Section: Methodsmentioning
confidence: 99%
“…Our results indicate that while stimulation artifacts can contaminate signals recorded from DRG neurons, there was not a significant impact upon limb position estimates. Preliminary results have been presented in poster form at conferences [34, 35]. …”
Section: Introductionmentioning
confidence: 99%
“…Finally, the current was maintained in 0.5 mA and the frequency was lowered to 3 Hz (experiment #4), which gave rise to a positive effect on axonal growth, showing an increased axonal extension and axonal sprouting for the electrically stimulated DRG, compared with the non-stimulated ones. Several studies of neurostimulation of DRG have observed that low frequencies (<20 Hz) have a beneficial effect on pain relief, inducing the dorsal horn of the spinal cord inhibition via the activation of low threshold mechanoreceptors and the release of endorphins and dynorphins [ 76 , 77 , 78 , 79 ]. Therefore, we could say that the applied stimulation frequency of 3 Hz is within the physiological range of DRG activation.…”
Section: Resultsmentioning
confidence: 99%
“…To implement DRG feedback in a walking device, decoded predictions of hind limb state must be calculated in real time. Recently, limb locations were predicted from DRG recordings in real time and used to control intramuscular stimulation patterns in cats (Bauman et al , 2011; Bruns et al , 2013). The algorithm moved the leg sequentially to one of four quadrants based on predicted limb location.…”
Section: Introductionmentioning
confidence: 99%